Building the image of city through organizational support and community commitment - Juanim, Juanim; Ratnamiasih, Ina (International Journal of Engineering and Technology, 2018)
This research is in progress to meet the overall research grant on the city's image. Images are a very important thing for a city. With a good image of the city, will bring many tourists, businessmen, as well as investors. this will certainly encourage the increase in income expected by the community, along with the image of the city is increasing. Bandung is one of Indonesia's unique city. The city is constantly trying to improve its brand image. to improve the brand image of Bandung city influenced by several variables, the most influential is community commitment and government support. The results of the research with the spread of questionnaires on 100 respondents, proved that community commitment and organizational support greatly influenced the increase of brand image of the city of Bandung. Several recommendations have been given to support the improvement of the brand image of the city of Bandung, especially recommendations on how to improve organizational support and community commitment.Â